PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI TOKO BANDUNG BOOK CENTRE - Dessy Katana; Prihartono Prihartono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aimed to analyze the price and quality of service, how far the relationship with consumer satisfaction Bookstore Bandung Book Center. This study uses the associative method with a quantitative approach. Obtaining data from respondents through questionnaire answers. The data collection technique in this study was a questionnaire, namely through direct distribution with consumers at the Bandung Book Center Store. The population in the study amounted to 100 consumers. The sample taken is 50 consumers with random sampling. Data analysis using multiple linear regression. The results of this study indicate that Price (X1) has a positive and significant effect on customer satisfaction (Y) and Service Quality (X2) has a positive and significant effect on customer satisfaction (Y). Other results, that together price and service quality have a positive and significant effect on customer satisfaction. Companies must be able to ensure that they provide prices and quality services that match the wishes of consumers so that the company can survive and grow rapidly.